Intercostal hemangioma of the chest wall - Dzian, Anton; Hamzík, Julian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The authors describe a case of a 36-year-old patient who had six months’ pain of the thoracic spine and left chest. A soft slowly growing resistance was present on the dorso-lateral side of the left chest wall, in the range of the seventh to ninth rib. According to the medical history, the patient did not have any prior trauma and malignancy. A well-defined tumor of the left chest wall with calcifications, which grew to the seventh and eighth intercostal space, was present on computed tomography (CT) and magnetic resonance (MR) scans. The patient underwent resection of the tumor with the chest wall and reconstruction with polypropylene mesh. Histologically, it was a venous hemangioma, one of very rare tumors of the chest wall.